Designing of carbon nanotube/polymer composites using melt recirculation approach: Effect of aspect ratio on mechanical, electrical and EMI shielding response. (25th December 2015) - Verma, Pawan; Saini, Parveen; Choudhary, Veena
ABSTRACT: The paper describes the effect of aspect ratio of multiwall carbon nanotubes (MCNTs) on the electrical, mechanical and electromagnetic properties of polypropylene random copolymer (PPC). Long and short MCNTs with aspect ratio of 1356–1937 and 158 respectively were melt-blended with PPC in a micro twin screw extruder with melt recirculation that allow the formation of composites having 15 wt.% MCNTs. The good dispersion was confirmed by scanning electron microscopy and observation of electrical conductivity at low percolation threshold (0.45 and 1.07 wt.% for l- & s-MCNT/PPC composite respectively) and improvement of modulus and strength. The 15 wt.% l-MCNTs and s-MCNT loaded composites show 52% and 60% improvement in modulus respectively and 20% & 18% improvement in strength over neat PPC. The electromagnetic interference (EMI) shielding response (in 8.2–12.4 GHz frequency range) revealed that l-MCNT based PPC composites display better shielding at lower loading (up to 4 wt.%) while s-MCNT show better attenuation at higher loadings. The realization shielding effectiveness value of − 27 dB (> 99% attenuation) respectively for l-MCNT composites: and − 37 dB (> 99.9% attenuation) for s-MCNTs composites at 15 wt.% reflect their potential for making light weight and structurally strong EMI shields. Graphical abstract: Highlights: High shear melt-blending technique with recirculation approach was used for the preparation of nanocomposites. Aspect ratio and loading of MCNTs showed a significant effect on the shielding response of composites. Higher shielding effectiveness of PPCP-MCNT composites with > 99.9% attenuation can find applications as EMI shields.